PENGGUNAAN MEDIA AUDIO VISUAL UNTUK MENINGKATKAN KEMAMPUAN MEMBACA PUISI SISWA KELAS V SDN 94 PEKANBARU - Rumaina, Difa; Hamizi, Hamizi; Erlisnawati, Erlisnawati (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2014)
Abstrak This study departed from the low ability of fifth grade students of SDN 94 Pekanbaru in reading poetry. Formulation of the problem in this study is " Does the use of audio-visual media can enhance the ability to read poetry fifth grade students of SDN 94 Pekanbaru ?". The purpose of this research is to improve the ability to read poetry fifth grade students of SDN 94 Pekanbaru. The study subjects were 30 students consisting of 15 men and 15 women. Data were collected through observation using the observation sheet for the teacher and student activity data. The results of students' ability to read poetry performed Deuteronomy End of Cycle I and II. Teacher activity at the first meeting of the first cycle is 56.36 % categorized enough, at the second meeting of the first cycle increased to 76.36 % categorized either. At the second meeting of the second cycle increased to 80.00 % categorized well, and at the second meeting of the second cycle again increased to 89.09 %. Activities of students in the first cycle the first meeting fairly categorized 54.55 %, at the second meeting increased to 65.45 % categorized enough. At the first meeting of the second cycle increased by 72.73 % return either category, and at the second meeting of the second cycle again increased to 78.18 %. Preliminary data literacy poetry fifth grade students of SDN 94 Pekanbaru of 30 students only 2 people (6.67%) is said to be complete, while 28 ( 93.33 % ) did not complete. With an average value of 57,56. At the end of the first cycle increased Deuteronomy, of the 30 students who completed said as many as 20 students ( 66.66 % ) who did not complete 10 students (33.33%), with an average value of 65. In Deuteronomy End of Cycle II again increased from 30 students who completed as many as 28 (93.33%), while students who did not complete as much as 2 students (6.66 %). In Deuteronomy End of Cycle II in classical completeness of 93.33%. Because at the end of Deuteronomy classical completeness Cycle II has reached 80% it does not continue next siklus . From the above explanation shows that the use of audio-visual media can enhance the ability to read poetry fifth grade students of SDN 94 Pekanbaru . Keywords:Audio-Visual Media,Read Poetry